MODERNIZING DISTANCE EDUCATION SYSTEM IN THE DIGITAL ERA: A CASE STUDY OF INTERNATIONAL OPEN UNIVERSITY (IOU) - Hartono, Haryani Santo (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The development of technology is unavoidable. All fields are transforming digitally, including education. This journey of digitization began even before entering pandemic era that required everyone to interact online. International Open University (IOU), is an online-based Islamic campus that already has international accreditation. Carrying a mission as an Islamic higher education institution, IOU offered modern distance education system in the digital era.  By using qualitative methods with a case study, this study aims to describe the digital teaching and learning system conducted by IOU. This research seeks to explore forms of modern distance education in an Islamic higher education, which in turn can contribute to create a future of education that is inclusive, professional, and well-being.